An Operations management study on Le Jean de Marithe Francois Girbaud - Dimaano, Jenry P. (College of Engineering, 2005)
In this study,the group documented and conducted an analysis of the SM Megamall branch of Le Jean de Marithe Francois Girbaud using various methods on Operations Management. Information relevant to the study were acquired through a series of interviews with key personnel and a series of store visits. Sales data and purchase orders were the major information acquired by the group. All relevant data were identified and analyzed with the aid of a problem identification tool, which is the Streamline Diagnosis Diagram. Through this, the group was able to determine the root cause of all the problems and its main effect. It was proven and verified that the root cause is having no basis in making purchase orders. In effect, this contributes to the store not having enough space in the stockroom. Accordingly, the group focused on the analysis on inventory management. In the analysis, the stockroom was assumed to be of infinite capacity. Various tools were used to determine the top sellers in the store. By conducting Pareto Analysis and ABC Analysis, it was established that 80% of the store sales were contributed by 20% of the total number of available products. These products were determined to be bags, wallets and shoes (unisex). Having determined these products, the group focused their analysis of the store's inventory management. Results show that on average the store has 46% excess inventory, there were occurrences of pull-out items (average of 0.1 occurrence per month), trans-in (average of 5.5 occurrences per month), trans-out (average of 3.8 occurrences per month), and usage of fitting rooms ( 4 times for year 2004) as an extension of stockroom. These problems were addressed by the group by determining the best model to use for the Girbaud inventory systems. With the store having fixed reorder periods. Monday and Thursday, with lead time equal to 3 and 4 days respectively, the applicable model was Fixed-Order Interval Model. Analysis of the other possible models that could be used was conducted. It is concluded that the Fixed order interval model with constant average demand was the best model for the Girbaud inventory system. Certain assumptions are: (1) only one SKU is involved, (2) demand for the SKU from the previous week is known, (3) There is a constant average demand level with random variations around the average, (4) lead time equals order interval, (5) protection interval is 7 days, (6) Service level is 99%, and (7) there are no back orders. Using the model stated above together with its assumptions, the group created a program for the Girbaud model using the programming language of Visual Basic 6.0 to compute for the order quantities of various product lines or SKUs that would be ordered. The proposed Girbaud model was validated by running data gathered from the past year to the program made. Validation results show that the number of orders received improved for all twelve months (year 2004). The highest of which is a 69.4% improvement in the month of July and the lowest is a 26.3% improvement in the month of March. The model was validated using values from the actual sales volume for the year 2004, and it has shown an improvement for all months. The group recommends that this Girbaud model be used to compute for order quantities for particular SKUs. Results of the study would be used by the company as a benchmark for improving service systems of their own stores.